Penerapan Material Requirements Planning terhadap Pengendalian Persediaan Bahan Baku Home Industry Palangka Raya - Setianto, Tito; Harinie, Luluk Tri; Syamsudin, Achmad; Giovanni, Jonathan (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2025)
This study aims to analyze the efficiency of raw material inventory control in a home-based cake production industry in Palangka Raya through the application of the MRP method. The main issue faced is inefficiency in inventory management, leading to an accumulation of raw materials and increased storage costs. Therefore, a method is needed to optimize raw material orders so that they align more closely with production needs. This study employs a quantitative descriptive approach, using demand forecasting techniques with the Linear Regression method, which has been proven to have a lower error value compared to other methods. The MRP analysis is conducted using the LFL, EOQ, and POQ techniques. The findings indicate that the POQ method results in the lowest total inventory cost of Rp3,969,500, making it more efficient than the LFL and EOQ methods. These results demonstrate that the implementation of MRP can enhance the efficiency of raw material inventory management, reduce storage costs, and minimize the risk of overstocking. This study contributes by providing an MRP-based solution for home industries and small-medium enterprises (SMEs) to optimize inventory management. Furthermore, it serves as a reference for future research in the fields of inventory control and supply chain management. Keywords: Inventory control; Material Requirement Planning (MRP); Lot Sizing; Forecasting; Cost Efficiency